Phenomenology of sprinting and endurance: toward a uniform performance assessment model - Westera, W. (New Studies in Athletics, 2011)
According to the IAAF scoring tables, Usain Bolt`s 100m world record of 9.58 sec is worth 1374 points, whereas Kenenisa Bekele`s 10,000m world record of 26:17.59 yields only 1295 points. This suggests a weakness in the current scoring methodology.